Synthesis of Hierarchical SnO2 Nanowire–TiO2 Nanorod Brushes Anchored to Commercially Available FTO-coated Glass Substrates - Miller, Derek R.; Akbar, Sheikh A.; Morris, Pat A. (Nano-Micro Letters, 2017)
Growth of single-crystal SnO2 nanowires using a fluorine-doped SnO2 (FTO) thin film as both the source and substrate is demonstrated for the first time at relatively low temperature (580 °C) which preserves the integrity of the underlying glass support and improves scalability to devices. Furthermore, a microwave hydrothermal process is shown to grow TiO2 nanorods on these nanowires to create a hierarchical nanoheterostructure that will lead to efficient photogenerated charge carrier separation and rapid transport of electrons to the substrate. This process simplifies nanowire growth by using commercially available and widely used FTO substrates without the need for an additional upstream Sn source and can be used as a high surface area host structure to many other hierarchical structures. Highlights: 1 Single-crystal SnO2 nanowires can be grown from polycrystalline thin films of fluorine-doped SnO2 (FTO) on glass substrates at a reduced temperature of 580 °C without the need for an upstream source powder. 2 A novel hierarchical nanobrush-like structure was designed to maximize the surface area of the photoactive material while aiding more efficient photogenerated charge carrier separation and extraction through the nanowire core for photocatalysis and dye-sensitized solar cells. 3 The SnO2 nanowires were used as an anchored 3D host to create a novel hierarchical nanobrush-like structure, and this immobilized structure was designed to maximize the surface area of the photoactive material while aiding more efficient photogenerated charge carrier separation and extraction through the nanowire core for photocatalysis and dye-sensitized solar cells.